Evaluating the disinfection efficacy of low-pressure ultraviolet irradiation on river water - Sivhute, Elizabeth Musigeni (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScFoodSc)--Stellenbosch University, 2019.